Strategi Pembelajaran Tahfidz Al-Qur’an, Pondok Tahfidz Putri Anak-Anak - Subaidi; Barowi; Sutarno (Proceedings of Annual Conference on Islamic Educational Management, 2022)
This study aims to describe the learning strategy of tahfidz al-Qur’an at Pondok Tahfidz Putri for Yanăbî’ul Qur’an Children in Sambeng Karangmalang Gebog Kab.Kudus. In this study using a qualitative approach, taking the research location at Pondok Tahfidz Putri Anak Yanăbî’ul Qur’an Sambeng Karangmalang Gebog Kab.Kudus. Data collection techniques through interviews, observation, and documentation. While the data analysis with data reduction steps, data presentation, and drawing conclusions. The results of the study concluded that the tahfidz al-Qur’an learning strategy had an impact on increasing the success of children in memorizing the Qur’an. The process of learning tahfidz al-Qur’an is carried out using various strategies, including; musyafahah (face to face), takrir, muraja ’ah, mudarasah, test and halaqah method. Inhibiting factors in learning tahfidz al-Qur’an include: for children and converts sometimes they are unable/sick; children mostly like to play and lazy to memorize; long year-end holidays; children’s visits by the guardians outside the stipulated hours; affected by the external environment, as a result of the permission to go home not at the time of return.